2000
DOI: 10.1364/josaa.17.000538
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual and topographical variation of L:M cone ratios in monkey retinas

Abstract: We analyzed the ratio of L:M cone photopigment mRNA in the retinas of Old World monkeys, using the method of rapid polymerase chain reaction-single-strand conformation polymorphism. The L:M cone pigment mRNA ratio in whole retina ranged from 0.6 to 7.0, with a mean of approximately 1.6 (standard deviation, +/- 0.56; n = 26). There was no change in this ratio with eccentricity up to 9 mm (approximately 45 degrees), though the ratio was approximately 30% greater in temporal than in nasal retina. The mRNA ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 28 publications
6
39
0
1
Order By: Relevance
“…The ERG estimates of L:M ratio reflect the cone ratio from an ϳ70°field, whereas the AO estimates are derived from relatively small (ϳ0.5°) patches of retina. The close agreement between the two techniques corroborates previous reports that the local ratio of L to M cones varies little within the central ϳ70° (Hagstrom et al, 1998;Deeb et al, 2000;Knau et al, 2001) (but see Albrecht et al, 2002). The histogram in Figure 7 shows that the range in L:M cone ratio for our seven male subjects reflects the overall range in the normal male population, based on the previously published ERG results .…”
Section: Comparison With Erg-derived Estimates Of L:m Ratiosupporting
confidence: 90%
See 4 more Smart Citations
“…The ERG estimates of L:M ratio reflect the cone ratio from an ϳ70°field, whereas the AO estimates are derived from relatively small (ϳ0.5°) patches of retina. The close agreement between the two techniques corroborates previous reports that the local ratio of L to M cones varies little within the central ϳ70° (Hagstrom et al, 1998;Deeb et al, 2000;Knau et al, 2001) (but see Albrecht et al, 2002). The histogram in Figure 7 shows that the range in L:M cone ratio for our seven male subjects reflects the overall range in the normal male population, based on the previously published ERG results .…”
Section: Comparison With Erg-derived Estimates Of L:m Ratiosupporting
confidence: 90%
“…We also observed a departure from random assignment of photopigment on a large spatial scale in subject AP whose L:M ratio was 1.24 (55.4% L) in nasal retina and 1.77:1 (63.9% L) in temporal retina. Deeb et al (2000) reported a similar nasal-temporal asymmetry in L:M cone ratio in the monkey retina. Conversely, Roorda and Williams (1999) found very similar L:M cone ratios at two foveal locations in one subject (subject JW).…”
Section: Mechanisms That Determine the Relative Numbers And Arrangemementioning
confidence: 65%
See 3 more Smart Citations